2021
DOI: 10.1371/journal.ppat.1009856
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of protection after maternal immunization for respiratory syncytial virus in cotton rats

Abstract: Maternal anti-respiratory syncytial virus (RSV) antibodies acquired by the fetus through the placenta protect neonates from RSV disease through the first weeks of life. In the cotton rat model of RSV infections, we previously reported that immunization of dams during pregnancy with virus-like particles assembled with mutation stabilized pre-fusion F protein as well as the wild type G protein resulted in robust protection of their offspring from RSV challenge. Here we describe the durability of those protective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…The presence of G (H/G) in the VLPs did not make a statistically significant difference in the levels of total anti-pre-fusion F IgG antibodies induced using either mutant stabilized pre-F as target (Figure 4, panels A, B). As we have previously noted, however, the levels of total anti-pre- F IgG antibodies detected with the soluble UC-3 F protein target were consistently slightly higher than the levels detected with the soluble DS Cav1 F protein target, but the differences were not statistically significant (36).…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…The presence of G (H/G) in the VLPs did not make a statistically significant difference in the levels of total anti-pre-fusion F IgG antibodies induced using either mutant stabilized pre-F as target (Figure 4, panels A, B). As we have previously noted, however, the levels of total anti-pre- F IgG antibodies detected with the soluble UC-3 F protein target were consistently slightly higher than the levels detected with the soluble DS Cav1 F protein target, but the differences were not statistically significant (36).…”
Section: Resultsmentioning
confidence: 63%
“…One was the soluble version of the DS-Cav1 mutant F protein. The other was a soluble version of another mutant stabilized, but uncleaved pre-fusion F protein which we have characterized previously, UC-3 pre-fusion F protein (20, 32, 35, 36). Inclusion of the UC-3 F target was because we have detected differences between the two targets in assessing induced anti-RSV antibodies (20, 32, 36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies in the cotton rat model of maternal immunization using a novel virus-like particle (VLP) vaccine candidates assembled with different pre-fusion RSV F proteins along with the RSV G attachment protein showed that maternal vaccination improves protection in young animals (at 4 weeks after birth). 20 Here, we show that maternal vaccination also protects litters from lung pathology and cytokine gene expression early on, but not later in life as maternal antibodies in the litter wane. Importantly, we find that maternal vaccination results in an increase in mRNA expression for IL-6 and IFNγ in the lung when RSV infection occurs later in the life of the litters, and when protection from RSV by matAbs wanes or cannot be detected, correlating with the modulation of the litter’s response to RSV in their lung.…”
Section: Introductionmentioning
confidence: 69%